Pengaruh celebrity worship terhadap body image pada remaja dimoderasi oleh self-esteem - Munawwarah, Nadia Salsabila; Cahyaning Suryaningrum (Universitas Muhammadiyah Malang, 2024)
Body image is a conscious representation that can form positive or negative judgments. Negative body image isoften associated with celebrity worship. A person’s personality influences their body image. Personality traits includeself-esteem. Individuals with high self-esteem will not be obsessed with the body standards depicted by their favoritecelebrities which can lead to a negative body image if they cannot achieve the standards depicted. Self-esteem as amoderator variable is expected to be able to moderate the influence of celebrity worship on body image. The researchmethod used was quantitative with a moderated research design on 287 teenagers aged 16-18 years who liked K-popand Korean culture. The research instruments used were the Celebrity Attitude Scale (CAS), Body Image DisturbanceQuestionnaire (BIDQ), and Self Esteem Scale. Data analysis in this study used Moderated Regression Analysis (MRA).The results showed that self-esteem could not moderate the influence of celebrity worship on body image.